The Influence of Jigsaw Technique and Learning Style toward Students’ Essay Writing Achievement to the Fourth Semester Students of STAIN Curup in the Academic Year of 2013-2014 - Harpiansi Harpiansi (Universitas PGRI Palembang, 2013)
AbstractThis research aimed at evaluating the significant influence of Jigsaw technique towards students’ Cause and Effect essay writing achievement, the significant influence of learning styles toward Students’ Cause and Effect essay writing achievement, and significant interaction between Jigsaw technique and learning styles toward students Cause and Effect essay writing achievement. In doing research, the writer used experimental method with factorial design. This research was conducted at STAIN Curup with the sample 72 students where 36 studentsparticipated in Experiment group and 36 students participated in Control group. In analyzing the data, independent t-test One Way ANOVA and two-way ANOVA were used. The findings of the study showed that there was significant influenceof Jigsaw technique towards students cause and effect essay writing achievement, there was no significance influence of learning styles towards students Cause and Effect essay writing achievement and there was no significant interaction between Jigsaw technique and Learning styles toward students cause and effect essay writing achievementKey words: Jigsaw, Learning Styles, Cause and Effect Essay Writing